2018
DOI: 10.14444/5088
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Osteomyelitis: A Comparison of Associated Outcomes in Early Versus Delayed Surgical Treatment

Abstract: Background: The recommended timing of surgical intervention for vertebral osteomyelitis (VO) is controversial; however, most studies are not sufficiently powered. Our goal was to investigate the associated effects of delaying surgery in VO patients on in-hospital complications, neurologic deficits, and mortality.Methods: Retrospective review of the National Inpatient Sample. Patients who underwent surgery for VO from 1998 to 2013 were identified using codes from the International Classification of Disease, Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
1
25
0
3
Order By: Relevance
“…Third, the timing of surgical intervention for PVO remains controversial [3]. Segreto et al found an immediate operation defined by within 24 hours of admission may reduce complications and mortality among patients with PVO in a claim database [28]. Other studies based on single-center experience showed no significant benefit from early abscess drainage [29, 30], which was consistent to our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Third, the timing of surgical intervention for PVO remains controversial [3]. Segreto et al found an immediate operation defined by within 24 hours of admission may reduce complications and mortality among patients with PVO in a claim database [28]. Other studies based on single-center experience showed no significant benefit from early abscess drainage [29, 30], which was consistent to our findings.…”
Section: Discussionsupporting
confidence: 87%
“…2 Delaying a necessary surgical intervention is associated with an increased mortality and morbidity. 24…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Bernard et al [70]a high proportion (44%) of patients were treated with predominantly oral antibiotics; with 52% of patients overall receiving intravenous treatment for less than 14 days in a non-standardised fashion. The results from the OVIVA study [73] , a recently A study by Segreto, et al evaluated the outcomes of early (less than 24 hours) versus delayed surgical treatment of VO using a large nationwide inpatient database [3]. This study found that VO patients who underwent surgery after 24 hours of admission had higher likelihood of morbidity and mortality.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Prior studies report conflicting findings. While some authors have found an advantage to earlier surgical intervention, others have not been able to show benefit[3]. All these studies are limited.…”
mentioning
confidence: 98%